Community Health Assessment for Hodgeman County Kansas - McCullough-Culver, Sheila (My University, 2014)
A Community Health Assessment (CHA) is the base on which a community builds a plan for improving and promoting the health of county residents. For our purposes community and county shall be synonymous throughout this process. The purpose of a CHA is to identify factors and issues that affect or will affect the health of a population and help determine the availability of resources within the community. Through efforts among the community leaders, public health, area businesses, hospital, health care providers and residents we can answer questions such as: “What concerns do our community residents have?”, “What are the resources needed in our county we currently do not have?”, “What are the community strengths?”, and “What are the community health deficiencies?” Community-based assessment is the first step in the community health planning process. This report will describe the community health process for Hodgeman County Kansas from the beginning of the CHA to the completion of the assessment and presentation to the community. The assessment starts with the people who reside within the community and continues to involve the citizens through the implementation of strategies that are developed. This process ensures that the CHA is done by the community and not on the community. This report presents the details of completing a CHA on Hodgeman County at the Hodgeman County Health Department in Jetmore, Kansas. This CHA was facilitated by Sheila McCullough-Culver, a MPH candidate. The report describes the details and process of completing a CHA for the purpose of community improvement. Following the process set forth by the North Carolina Division of Public Health the CHA process provided sound and evidence–based procedures that guided our CHA team from start to the final identified health priorities. Additionally this CHA allowed the county health department to attain a start in its goal of accreditation through the Public Health Accreditation Board (PHAB). A Community Health Assessment Team (CHAT) was formed and through a series of five meetings health priority strengths and concerns for Hodgeman County were determined by the CHAT team. Primary and secondary data was gathered, and through the CHA process it was analyzed, interpreted, and it was determined what Hodgeman county health priorities were, giving community members a baseline on which strategic plans can be built. The primary method of information gathering was a community survey on Hodgeman County. The survey consist of 51 questions divided into seven categories: (a) quality of life statements, (b) community improvements, (c) health information, (d) personal health, (e) access to care/family health, (f) emergency preparedness, and (g) demographic questions. This survey was available in printed and online versions; also English and Spanish language versions were available. At the completion of the information gathering phase health priority list were constructed using primary data, the CHA, secondary data from Kansas Health matters and County Health Rakings. The top fifteen health priorities were taken to the community meeting and further narrowed down to the top three health priorities as the community saw it.
Keywords: Community health assessment; Hodgman county; Kansas; Public Health (0573)